Exploring the mechanism of consumer purchase intention in a traditional culture based on the theory of planned behavior - Zong, Zupan; Liu, Xinyu; Gao, Huijing (Frontiers in Psychology, 2023)
There has been a growing interest among scholars and practitioners in cultural empowerment due to the importance of this subject. In this study, we aim to explore the connection between traditional cultural symbols and cultural identity, further estimating how two variables stimulate consumers’ emotional value to generate consumers’ purchase intention. Based on existing traditional cultural literature and the theory of planned behavior (TPB), we first proposed a research framework and then empirically tested the relationship among traditional culture symbols, cultural identity, emotional value, and consumers’ purchase intention. The survey data was tested using structural equation modeling (SEM) and the following conclusions were drawn. First, the cognition of traditional cultural symbols and cultural identity has a direct and significant impact on the emotional value thereby, eliciting consumers’ purchase intention. Second, traditional cultural symbols are directly and indirectly (i.e., through emotional value or cultural identity) positively associated with consumers’ purchase intention, also cultural identity is directly and indirectly (i.e., through emotional value) associated with consumer purchase intention. Finally, emotional values mediate the indirect effect of traditional culture and cultural identity on purchase intention, and cultural identity plays a moderating role between traditional cultural symbols and consumers’ purchase intention. Our findings help to expand the existing literature on consumer purchase intentions by rationally using traditional cultural symbols in the product design and suggesting relevant marketing strategies. The research results can provide valuable inspiration for promoting the sustainable development of the national tidal market and repeating consumers’ purchasing intentions.